A day with PERMATA / E. Tavasuria Elangovan - Elangovan, E. Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
On April 26, 2019, a programme called ‘Sehari Bersama Anak Permata’ was organized by ASeT (Applied Sciences Tapah As sociation), UiTM Perak Branch, Tapah Campus at the Autism care center; My Star Autism, Ipoh. A Total of 31 students and 4 lecturers from Faculty of Applied Science (FSG) were involved in this programme. The objectives of the programme were to incul-cate the noble attributes among the FSG students such as loving, caring, helpful and generous attitude through friendly engage-ment with autism children, to provide opportunities for students to sharpen their leadership skills through teamwork and group activities, to practice communication skills in a challenging en-vironment and to enhance the professionalism and credibility of the students and lecturers.